Negative electrode sheet, battery, and electric device

CN122455676BActive Publication Date: 2026-10-09CALB GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610923913.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-09
Estimated Expiration
2046-06-25

AI Technical Summary

Technical Problem

[0003]本申请的主要目的在于提供一种负极片、电池和用电设备,以解决现有技术中硅基材料在负极片上分布不均匀,导致锂离子传输速率差异大,进而影响电池动力学性能的问题

Benefits of technology

[0011]By applying the negative electrode provided in this application, the uniformity coefficient c of silicon element distribution in the negative electrode active material layer and the porosity p of the negative electrode active layer are adjusted to satisfy: 0.05≤c×p≤1.1. This overcomes the kinetic performance fluctuations caused by the heterogeneity of active component distribution, improves the kinetic consistency of different positions of the electrode, and takes into account the kinetic performance of the electrolyte on the negative electrode, thus significantly improving the kinetic performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a negative plate, a battery and an electric device, and belongs to the technical field of batteries. The negative plate comprises a negative active layer, the negative active layer comprises a negative material, the negative material comprises a negative active material, the negative active material comprises a silicon-based material and a carbon material; the uniformity coefficient c of the silicon element in the silicon-based material in the negative active layer and the porosity p of the negative active layer satisfy: 0.05<=c*p<=1.1; c=c max / c min ; c max is the maximum value of the mass content of the silicon element in all the to-be-tested regions, c min is the minimum value of the mass content of the silicon element in all the to-be-tested regions, the number of the to-be-tested regions is n, and n is an integer greater than or equal to 3. Through accurate control of the uniformity coefficient of the silicon element in the silicon-based material in the negative active layer and the porosity of the negative active layer, the consistency of the lithium ion transmission rate is improved through the synergistic effect of the two aspects, and the overall kinetic performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and more specifically, to a negative electrode, a battery, and an electrical device. Background Technology

[0002] In actual production, due to limitations in the slurry mixing and coating processes, silicon-based materials and graphite materials may aggregate or agglomerate to varying degrees in different regions of the anode sheet. The dispersion of silicon and graphite in the anode sheet is uneven. The electronic conductivity of silicon and graphite is different, with silicon having relatively poor electronic conductivity. This leads to differences in lithium-ion transport rates, resulting in inconsistent dynamics at different positions of the electrode sheet, which in turn affects the dynamic performance of the battery. Summary of the Invention

[0003] The main objective of this application is to provide a negative electrode, a battery, and an electrical device to solve the problem in the prior art where the uneven distribution of silicon-based materials on the negative electrode leads to large differences in lithium-ion transport rates, which in turn affects the battery's dynamic performance.

[0004] To achieve the above objectives, according to one aspect of this application, a negative electrode sheet is provided, comprising a negative electrode active layer, the negative electrode active layer comprising a negative electrode material; the negative electrode material comprising a negative electrode active material; the negative electrode active material comprising a silicon-based material and a carbon material; the uniformity coefficient of silicon element distribution in the silicon-based material in the negative electrode active layer and the porosity of the negative electrode active layer satisfy relationship I:

[0005] 0.05≤c×p≤1.1 Formula I;

[0006] In Equation I, c is the uniformity coefficient of silicon element distribution in the negative electrode active layer of silicon-based material; p = 3.5%~85%; p is the porosity of the negative electrode active layer;

[0007] c=c max / c min Formula II;

[0008] In Equation II, c max c is the maximum mass content of silicon in all tested regions. min Let n be the minimum mass content of silicon in all regions to be tested, where n is an integer greater than or equal to 3.

[0009] According to a second aspect of this application, a battery is provided, including a cell; the cell includes a positive electrode and a negative electrode; the negative electrode is the aforementioned negative electrode.

[0010] According to a third aspect of this application, an electrical device includes a battery; the battery is the aforementioned type of battery.

[0011] By applying the negative electrode provided in this application, the uniformity coefficient c of silicon element distribution in the negative electrode active material layer and the porosity p of the negative electrode active layer are adjusted to satisfy: 0.05≤c×p≤1.1. This overcomes the kinetic performance fluctuations caused by the heterogeneity of active component distribution, improves the kinetic consistency of different positions of the electrode, and takes into account the kinetic performance of the electrolyte on the negative electrode, thus significantly improving the kinetic performance of the battery. Detailed Implementation

[0012] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present application will now be described in detail with reference to the embodiments.

[0013] As described in the background art, silicon-based materials may aggregate or cluster to varying degrees in different regions of the negative electrode, resulting in uneven distribution of silicon-based materials and consequently differences in lithium-ion transport rates. This inconsistency in kinetics leads to inconsistent lithium-ion insertion / extraction rates in some regions of the negative electrode, thereby affecting the kinetic performance of the battery.

[0014] To address the aforementioned issues of insufficient battery kinetic performance, according to one aspect of this application, a negative electrode sheet is provided, comprising a negative electrode active layer, the negative electrode active layer comprising a negative electrode material; the negative electrode material comprises a negative electrode active material; the negative electrode active material comprises a silicon-based material and a carbon material; the uniformity coefficient of silicon element distribution in the silicon-based material in the negative electrode active layer and the porosity of the negative electrode active layer satisfy relationship I:

[0015] 0.05≤c×p≤1.1 Formula I;

[0016] In Equation I, c is the uniformity coefficient of silicon element distribution in the negative electrode active layer of silicon-based material; p is the porosity of the negative electrode active layer.

[0017] c=c max / c min Formula II;

[0018] In Equation II, c max c is the maximum mass content of silicon in all tested regions. min The minimum mass content of silicon element in all regions to be tested is n, where n is an integer greater than or equal to 3.

[0019] In Formula I of this application, c×p can be any value from 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.0, 1.05, 1.1 or a range between any two.

[0020] The ratio of silicon mass content in different regions indirectly reflects the uniformity of silicon distribution. A larger ratio indicates poor uniformity of silicon-based material distribution in different regions, which can easily lead to poor electron transport and kinetic consistency in some areas, affecting the overall kinetic performance of the battery. When the uniformity coefficient of silicon distribution in the negative electrode active layer is large, reducing the porosity of the negative electrode sheet helps to improve the electron contact between particles, improve the conductivity at different locations, and reduce the difference in conductivity between different regions, thereby helping to reduce the difference in kinetic performance caused by uneven silicon distribution in different regions. When the uniformity of silicon distribution in different regions is high and the uniformity index is small, appropriately increasing the porosity helps to improve the wetting ability of the electrolyte and the ion transport efficiency. This application achieves a uniform distribution coefficient (c) of silicon in the negative electrode active layer and a porosity (p) such that 0.05 ≤ c × p ≤ 1.1. This creates a continuous electron and lithium-ion transport path, facilitating uniform lithium-ion diffusion across the entire electrode sheet, reducing local current density differences, and improving kinetic consistency. Simultaneously, it ensures good electrolyte wetting, reduces ion diffusion resistance, and enhances lithium-ion transport performance, thereby improving the overall kinetic performance of the battery. When c × p is too small, electrolyte wetting is impeded, resulting in poor overall battery kinetic performance. When c × p is too large, local current transport is poor, conductivity is weak, and kinetic consistency across different regions of the negative electrode sheet is poor, thus affecting the overall kinetic performance of the battery.

[0021] In the above embodiments of this application, c max and c min The following method was used to determine the silicon content: The battery was discharged at 0.33C to the lower limit voltage of 2.5V to obtain a fully discharged battery. Then, the battery was disassembled, the negative electrode was removed, and the battery was divided into n regions along its length. The silicon content in m different test areas of each region was tested. The maximum mass content of silicon in the n×m test areas was taken as c. max The minimum mass content of silicon in the n×m block of the test area is taken as c. min Furthermore, 1 to 5 different test areas are selected from each region for testing.

[0022] In this application, the preparation method of the silicon-based material is not specifically limited; specifically, the preparation method is as follows: A porous carbon material is used as the carbon matrix and added to a rotary kiln. First, it is sieved using an air classifier. The pressure inside the classifier is 100 Pa to 2000 Pa. Nitrogen gas is introduced to remove oxygen at a flow rate of 10 L / min to 20 L / min. The calcination heating rate is 5 °C / min to 10 °C / min, the temperature is 480 °C to 540 °C, and the rotary kiln rotation speed is 0.5 rpm to 3 rpm. While maintaining a constant calcination temperature, a mixed gas is introduced. The mixed gas includes nitrogen and silane in a volume ratio of 1:(1 to 4), with a flow rate of 0.2 L / min to 0.6 L / min and an introduction time of 50 min to 170 min. After the reaction is complete, the silane gas is turned off, and only nitrogen gas is introduced. The silicon-based material is calcined in a nitrogen atmosphere at a temperature of 550℃~600℃ for 60min~180min. When the temperature fluctuation gradually stabilizes, acetylene gas is introduced to carry out the reaction. The acetylene gas flow rate is set to 1L / min~3L / min. The deposition temperature is 500℃~600℃ and the deposition time is 10h~18h. After the reaction is complete, the gas is turned off and the material is allowed to cool naturally in a nitrogen atmosphere. After the temperature has completely cooled down, the material is demagnetized to obtain a silicon-based material with a carbon coating.

[0023] To further improve the consistency of lithium-ion transport rate and electronic conductivity of the negative electrode active layer, thereby enhancing the overall electrochemical performance of the battery, the relationship between the silicon-based material distribution uniformity coefficient and the porosity of the negative electrode active coating is further optimized. In some embodiments, in Equation I, 0.095 ≤ c × p ≤ 0.56. When the silicon dispersion uniformity coefficient and the porosity of the negative electrode active layer satisfy the above relationship, the consistency of lithium-ion transport rate is higher, and the electronic conductivity is higher, which helps to improve the overall kinetic consistency of the battery and enhance its kinetic performance.

[0024] To improve battery energy density while maintaining good electrochemical activity and stability, in some embodiments, c satisfies: 1.05 ≤ c ≤ 1.5. Specifically, but not limitingly, c can be any value from 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.5, or a range between any two. Further, c satisfies: 1.05 ≤ c ≤ 1.2.

[0025] Adjusting the uniformity coefficient of silicon distribution in different parts of the negative electrode active layer within the above range helps to improve the kinetic consistency of each region of the negative electrode sheet, thereby helping to improve the kinetic performance of the battery.

[0026] The method of adjusting c is not specifically limited in this application; specifically, it can be adjusted by controlling the stirring speed, time, and slurry settling time during the preparation of the negative electrode slurry. The stirring speed can be 3 rpm to 80 rpm, the time can be 1 h to 5 h, and the slurry settling time can be 0 h to 5 h. Increasing the stirring speed or time helps to improve the uniformity of silicon-based material distribution; shortening the settling time helps to reduce the risk of slurry sedimentation and also helps to improve the uniformity of silicon element distribution.

[0027] In some implementations, p satisfies: 3.5% ≤ p ≤ 85%. Specifically, but not limitingly, p can be any value from 3.5%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, or a range between any two. Further, p satisfies: 8% ≤ p ≤ 50%.

[0028] Controlling the porosity of the negative electrode active layer within the above range can ensure good electrolyte wetting, promote lithium-ion transport, reduce diffusion resistance, and also help to build a continuous conductive network, improve the electronic conductivity of the negative electrode active layer, thereby further improving the battery's dynamic performance.

[0029] The method for adjusting P is not specifically limited in this application. Specifically, it can be adjusted by regulating the rolling pressure during the negative electrode preparation process and the particle size of the silicon-based material. The rolling pressure can be 5T~30T; the particle size of the silicon-based material can be adjusted by regulating the grading and sieving steps during the silicon-based material preparation process, with the grading and sieving pressure being 100Pa~2000Pa. Increasing the rolling pressure reduces the porosity; the grading and sieving pressure is mainly used to control the particle size of the silicon-based material. By controlling the grading and sieving pressure, the particle size of the silicon-based material is reduced, thereby utilizing the silicon particles to fill the gaps and reduce the porosity.

[0030] In the application of silicon-carbon composite anode active materials, silicon-based materials have high theoretical capacity and low electronic conductivity, while carbon materials have relatively low theoretical capacity and high electronic conductivity. To balance the high theoretical capacity and reasonable electronic conductivity of silicon-carbon composite materials, and considering the uniformity of silicon material dispersion, the silicon content is particularly important. In some embodiments, the mass content of silicon in the anode active layer is less than or equal to 12%. Specifically, but not limitingly, the mass content of silicon in the anode active layer can be 2%, 4%, 6%, 8%, 10%, 12%, or any value within the range of any two of the above values. Controlling the mass content of silicon in the anode active layer within the above range helps improve the uniformity of silicon distribution in different parts of the anode sheet, and also helps improve the electronic conductivity of the anode material, thereby contributing to improving the kinetic consistency of the anode sheet and the overall kinetic performance of the battery.

[0031] Furthermore, I satisfies: 0.095 ≤ c × p ≤ 0.594; specifically, but not limitingly, c × p can be any value within the range of 0.095, 0.1, 0.2, 0.3, 0.4, 0.5, 0.55, 0.594, or any combination of two of the above values. When the mass content of silicon is within the above range, the control formula I satisfying the above conditions helps to further improve the overall kinetic performance of the battery.

[0032] Furthermore, the mass content of silicon in the silicon-based material within the negative electrode active layer is greater than or equal to 5% and less than or equal to 7.5%; that is, the mass content of silicon in the negative electrode active layer is controlled within the range of 5.0% to 7.5%; for example, any value among 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, and 7.5%, or any value within a range of two. By controlling the content of the silicon-based material within the above range, it is possible to ensure that the silicon-carbon negative electrode active material has both a high theoretical capacity and good electronic conductivity, and also to ensure the uniform and good dispersion of the silicon-based material in the negative electrode active layer, thereby improving the electrochemical performance of the lithium-ion battery.

[0033] In some embodiments, the mass content of silicon in the silicon-based material in the negative electrode active layer is greater than or equal to 12%; specifically, but not limitingly, the mass content of silicon in the negative electrode active layer can be 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, or any value within a range of any two of the above values. Controlling the mass content of silicon within the above range helps to optimize the energy density of the battery and improve its overall electrochemical performance.

[0034] Furthermore, Equation I satisfies: 0.05 ≤ c × p ≤ 0.635; specifically, but not limitingly, c × p can be any value within the range of 0.05, 0.08, 0.1, 0.12, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.635, or any combination of the above values. When the mass content of silicon in the negative electrode active layer is within the above range, adjusting Equation I to satisfy the above conditions helps to improve the uniformity of silicon distribution in various parts of the negative electrode, enhance the kinetic consistency of the negative electrode, and thus help to improve the kinetic performance of the battery.

[0035] Furthermore, the mass content of silicon in the negative electrode active layer of the silicon-based material is greater than or equal to 12% and less than or equal to 25%. Specifically, but not limitingly, the mass content of silicon in the negative electrode active layer of the silicon-based material can be 12%, 15%, 18%, 20%, 22%, 25%, or any value within a range of two of the above values. By controlling the mass content of silicon within the above range, it is helpful to improve the energy density of the battery while ensuring good kinetic performance.

[0036] There are various methods for detecting silicon content in the negative electrode active layer, and existing technologies can be selected according to actual needs. To improve the accuracy of the detection results and the ease of operation, in some embodiments, the silicon content is obtained using alkaline fusion-inductively coupled plasma elemental analysis (alkali fusion-ICP).

[0037] In practical applications, when silicon-based materials and carbon materials are used in combination, the compatibility and bonding between silicon-based materials and carbon materials, conductive agents, and other materials must be considered. For the silicon-based material, at least one of silicon-carbon composites, silicon suboxide, and nano-silicon can be selected. Simultaneously, at least one of artificial graphite and natural graphite can be selected as the carbon material. The negative electrode active material obtained by combining silicon-based and carbon materials using the above-mentioned types exhibits high energy density, cycle stability, and charge / discharge rate.

[0038] In some embodiments, the volume median particle size D of the negative electrode material V 50 satisfies: 4μm≤D V50 ≤ 10 μm; this particle size can be any value among 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm, or any value between two of them; for example, 5 μm to 9 μm. Controlling the volumetric median particle size Dv50 of the negative electrode material within the above range helps to improve the dispersion uniformity of particles in the slurry, which in turn helps to improve the distribution uniformity of silicon-based materials in the negative electrode active layer, improve kinetic consistency, and thus help to improve the kinetic performance of the battery; in addition, controlling the particle size within the above range also helps to shorten the ion transport path, further improving kinetic performance. The volume median particle size (Dv50) of the negative electrode material can be tested using a laser particle size distribution measuring instrument, including the following steps: 1) Pretreatment: The battery is discharged at 0.33C to the lower limit voltage of 2.5V. Empty electrode sheets are taken and immersed in dimethyl carbonate (DMC) solution at room temperature for 4 hours. After immersion, the electrode sheets are removed and dried in a vacuum environment. Active material powder on the surface of the electrode sheets is scraped off with a ceramic knife. Using a Mastersizer 3000, the particle size distribution is measured according to the particle size distribution laser diffraction method (specific steps refer to GB / T19077-2016). The particle size corresponding to the cumulative particle size distribution percentage reaching 50% is Dv50.

[0039] In some embodiments, the average particle size of the silicon-based material is greater than or equal to 3 μm and less than or equal to 12 μm; the average particle size of the carbon material is greater than or equal to 9 μm and less than or equal to 15 μm. Controlling the average particle size of both silicon-based and carbon materials within these ranges helps shorten the diffusion path of lithium ions within the negative electrode material particles, thereby accelerating the charge and discharge rate of lithium ions and improving the battery's kinetic performance. Within these particle size ranges, a larger specific surface area is provided, which is beneficial for improving the effective transport of electrons and lithium ions, enhancing the battery's charge and discharge capability at high rates. For silicon-based materials, the smaller particle size helps mitigate the volume expansion effect during charge and discharge, reduces interparticle stress, prevents material cracking and excessive SEI film growth, thereby improving cycle stability. Furthermore, controlling the average particle size of both silicon-based and carbon materials within these ranges also helps reduce the probability of agglomeration of silicon-based and carbon material particles during slurry preparation, improving the uniformity of silicon element distribution in the negative electrode active layer, and further contributing to improved battery kinetic performance.

[0040] In some embodiments, the compaction density of the negative electrode is 1.10 g / cm³. 3 ~1.75g / cm 3 Specifically, but not limitingly, the compaction density of the negative electrode can be 1.1 g / cm³. 3 1.2g / cm 3 1.3g / cm 3 1.4g / cm 3 15g / cm3 1.6g / cm 3 1.7g / cm 3 1.75g / cm 3 Any value in the range or any value between the two; for example, 1.3 g / cm³. 3 ~1.6g / cm 3 By adjusting the compaction density of the negative electrode within the aforementioned range, it is helpful to balance the energy density and ion transport performance of the battery, thus enabling the battery to have good overall electrochemical performance.

[0041] The test method for the compaction density of the negative electrode sheet includes the following steps: 1) Pretreatment: Discharge the battery at 0.33C to the lower limit voltage of 2.5V, take an empty battery, disassemble the electrode sheet, and soak the electrode sheet in dimethyl carbonate (DMC) solution for 4 hours; air dry; 2) Use a punching machine to punch the pretreated positive electrode sheet into circular pieces of a fixed area, denoted as S0. Take three circular pieces as parallel samples, and weigh the mass of the three circular pieces separately using an electronic balance, take the average value and record it as M1; use a micrometer... The thickness of the active material layer in each of the three discs (i.e., the total thickness of the negative electrode after removing the current collector) was measured, and the average value was recorded as H. Finally, an appropriate amount of deionized water was dropped onto each of the three discs, and the coating on the discs was gently wiped off with lint-free paper to expose the copper foil. The discs were left to stand at room temperature (or dried) for 10 minutes. After the copper foil was dried, the mass of the three copper foils was weighed, and the average value was recorded as M0. The compaction density of the negative electrode was obtained according to the following formula: A = (M1 - M0) / (H × S0).

[0042] In some embodiments, the negative electrode sheet includes a negative electrode current collector, and the negative electrode active layer is located on at least one side of the negative electrode current collector; the average roughness depth Rz of the surface of the negative electrode current collector is greater than or equal to 0.5 μm and less than or equal to 3 μm. The negative electrode current collector with the above-mentioned surface roughness has good mechanical contact with the negative electrode material layer, which helps to improve the electron transport performance between the negative electrode current collector and the negative electrode material layer, thereby helping to improve the dynamic performance of the battery. The test method for average roughness depth Rz is as follows: The lithium-ion battery is discharged at 0.33C to the lower limit voltage of 2.5V. The battery is disassembled and the negative electrode is removed. The negative electrode is soaked in dimethyl carbonate (DMC) solution for 2 hours and then dried to obtain the electrode to be tested. A diamond stylus with a tip curvature radius of 2μm is slowly slid along the foil surface of the electrode to be tested. Due to the unevenness of the foil surface of the electrode to be tested, the diamond stylus will move vertically in a direction perpendicular to the foil surface. Its vertical displacement is converted into an electrical signal by the sensor, and after amplification and processing, the surface roughness value Rz is displayed by the display instrument.

[0043] In some embodiments, the negative electrode current collector is copper foil or copper alloy foil. These materials are commonly used for negative electrode current collectors and possess excellent electron transport properties.

[0044] In some embodiments, the negative electrode sheet further includes a carbon layer located between the negative electrode current collector and the negative electrode active layer. The presence of a carbon layer between the negative electrode current collector and the negative electrode active layer significantly improves the electrical contact performance between them, provides additional electron transport channels, enhances coating adhesion, effectively buffers volumetric stress during charging and discharging, and improves the battery's kinetic and cycle performance.

[0045] In some embodiments, the thickness of the carbon layer is greater than or equal to 0.5 μm and less than or equal to 2 μm. Specifically, but not limitingly, the thickness of the carbon layer can be 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, or any value within a range of two of these values. Controlling the carbon layer thickness within this range helps improve the battery's kinetic performance and energy density. Carbon layer thickness testing method:

[0046] The carbon layer thickness test method is as follows: 1) Pretreatment: The battery is discharged at 0.33C to the lower limit voltage of 2.5V. The empty battery is taken out, the negative electrode is disassembled, and the negative electrode is soaked in dimethyl carbonate (DMC) solution for 4 hours; dried; the negative electrode is sliced ​​and the carbon layer thickness is tested by transmission electron microscopy.

[0047] In some embodiments, the negative electrode active layer includes a first negative electrode active layer and a second negative electrode active layer; the first negative electrode active layer and the second negative electrode active layer are sequentially disposed on the surface of the negative electrode current collector from the surface near the negative electrode current collector to the surface away from the negative electrode current collector. The first negative electrode active layer includes a first negative electrode active material, which includes a first silicon-based material and / or a first carbon material; the second negative electrode active layer includes a second negative electrode active material, which includes a second silicon-based material and / or a second carbon material; the average particle size of the first negative electrode active material is larger than the average particle size of the second negative electrode active material. Setting the average particle size of the first negative electrode active layer to be larger than that of the second negative electrode active layer, with larger particles on the surface, helps to form a suitable porosity on the surface, promotes lithium-ion transport, improves kinetic performance, and enhances kinetic consistency. By setting the first and second negative electrode active layers, the uneven distribution of silicon at different locations in the negative electrode active layer can be reduced, mitigating the risk of poor kinetic consistency at different locations and also reducing the requirements for the resistivity of the negative electrode material powder. This further improves the dispersion uniformity of silicon-based materials in the negative electrode active layer and enhances the overall kinetic consistency of the battery.

[0048] Specifically, but not limitingly, the first carbon material and the second carbon material are each independently selected from at least one of artificial graphite and natural graphite; the first silicon-based material and the second silicon-based material are each independently selected from at least one of silicon-carbon composite materials, carbon-coated materials of silicon-carbon composite materials, silicon suboxide, carbon-coated materials of silicon suboxide, and nano-silicon.

[0049] In some embodiments, the mass content of silicon in the second negative electrode active layer is greater than that in the first negative electrode active layer. Controlling the relative mass content of silicon in the second and first negative electrode active layers to meet the above conditions helps to provide sufficient space for the volume expansion of silicon-based materials during cycling, thereby helping to reduce the risk of cracking, pulverization, etc. of the negative electrode material and improving the cycle stability of the battery.

[0050] In some embodiments, the mass content of silicon in the second negative electrode active layer is less than the mass content of silicon in the first negative electrode active layer. Controlling the relative mass content of silicon in the second and first negative electrode active layers to meet the above conditions helps improve the lithium-ion transport performance on the surface of the negative electrode, thereby helping to improve the kinetic performance of the battery.

[0051] In some embodiments, the second negative electrode active material is a second carbon material; the first negative electrode active material is a composite of a first carbon material and a first silicon-based material. Screening the types of the first and second negative electrode active materials helps to improve the battery's kinetic performance.

[0052] According to a second aspect of this application, a battery is provided, including a cell; the cell includes a negative electrode and a positive electrode; the negative electrode is the aforementioned negative electrode.

[0053] In some embodiments, the positive electrode sheet includes a positive electrode active layer; the positive electrode active layer includes a positive electrode active material; the positive electrode active material is at least one of nickel-cobalt based positive electrode material and lithium iron phosphate material.

[0054] The structural formula of nickel-cobalt based cathode material is Li a Ni b Co x Mn d M e O2; where 0.75≤ a ≤1.2, b Greater than or equal to 0.8 b + x + d =1, 0≤ e≤0.2; M is selected from at least one of B, Zr, Ti, Si, Mo, La, Ce, Te, Nb, Ta, Al, W, Sr, V, Y, and Mg. The above nickel-cobalt based cathode materials exhibit good specific capacity, and their application in batteries helps improve battery energy density.

[0055] When the above-mentioned nickel-cobalt based positive electrode material is selected as the positive electrode active material, the negative electrode sheet satisfies: 0.095≤c×p≤0.451. By matching the material types and performance parameters of the positive and negative electrodes, it is helpful to significantly improve the energy density and dynamic performance of the battery.

[0056] The structural formula of lithium iron phosphate material is LiFe 1-u M' u PO v Q w Where u≤0.1, 3.85≤v≤4, 0≤w≤0.05, and M' is selected from at least one of Mn, Ni, Co, Cr, Cu, Bi, and Sb. Lithium iron phosphate materials have good safety and a certain energy density, and are widely applicable.

[0057] When the above-mentioned lithium iron phosphate material is selected as the positive electrode active material, the negative electrode sheet satisfies: 0.05≤c×p≤0.7227. Adjusting the performance parameters of the negative electrode sheet for specific positive electrode active materials helps improve the kinetic consistency of different regions of the negative electrode sheet and enhances the battery's kinetic performance.

[0058] In some implementations, when lithium iron phosphate is selected as the positive electrode active material, the mass content of silicon in the negative electrode active layer is ≤5%. Regulating the mass fraction of silicon within this range helps improve the uniformity of silicon distribution across different parts of the negative electrode, enhances the kinetic consistency across these parts, and thus helps improve the battery's kinetic performance.

[0059] In some embodiments, the battery cell includes a cylindrical cell. Because cylindrical cells experience high bending stress and expansion, leading to a high risk of lithium plating, the matching negative electrode preferably satisfies 0.05 ≤ c × p ≤ 0.5. These adjustments help improve the overall electrochemical performance of the battery cell.

[0060] In some embodiments, the battery includes an electrolyte; the electrolyte has an ionic conductivity of 8 mS / cm to 15 mS / cm at 25°C; and the battery is a lithium-ion battery. Adjusting the ionic conductivity of the electrolyte within the above range helps to improve lithium-ion transport performance and enhance the battery's kinetic performance.

[0061] In some embodiments, the electrolyte includes a lithium salt, a solvent, and additives; wherein the lithium salt includes at least one selected from lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalate borate (LiDFOP), and lithium hexafluorophosphate (LiPF6). The high ionic conductivity of these lithium salts in the solvent contributes to improving the kinetic performance of the battery.

[0062] In some embodiments, the concentration of lithium salt in the electrolyte is 0.8 mol / L to 1.2 mol / L. Regulating the lithium salt concentration within this range helps to balance ionic conductivity and electrolyte viscosity, thereby improving the battery's kinetic performance.

[0063] In some embodiments, the solvent is selected from at least one of cyclic carbonates, linear carbonates, and linear carboxylic esters. Specifically, but not limitingly, cyclic carbonates include at least one of ethylene carbonate, propylene carbonate, and fluoroethylene carbonate; linear carbonates include at least one of ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate; and linear carboxylic esters include at least one of ethyl acetate and methyl butyrate. These solvents exhibit good lithium-ion transport performance and can form a stable SEI film on the electrode surface, thereby contributing to improved battery kinetic and cycle performance.

[0064] In some embodiments, the additive includes fluoroethylene carbonate (FEC). By selecting the above-mentioned additive, it is helpful to improve the quality of the SEI film, mitigate local kinetic differences, and thus help to improve the overall kinetic performance of the battery.

[0065] In some embodiments, the mass percentage of the additive in the electrolyte is 1% to 10%; more preferably, the additive in the electrolyte is fluoroethylene carbonate. Controlling the mass percentage of the additive in the electrolyte within the above range helps to form a dense and uniform SEI film, thereby helping to improve the cycle life of the battery.

[0066] The battery in this application is a secondary battery, also known as a rechargeable battery or storage battery, which refers to a battery that can be used again after being discharged by recharging to activate the active materials.

[0067] Typically, a secondary battery includes an electrode assembly, an electrolyte, and an outer casing. The electrode assembly consists of a positive electrode, a negative electrode, and a separator. The electrode assembly and electrolyte are assembled inside the outer casing. During charging and discharging, active ions (such as lithium ions) move back and forth between the positive and negative electrodes, inserting and extracting. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing active ions to pass through. The electrolyte, located between the positive and negative electrodes, mainly serves to conduct active ions.

[0068] As an example, the preparation process of a secondary battery is as follows: the positive electrode, separator, and negative electrode are stacked in sequence, with the separator acting as a separator between the positive and negative electrodes. Then, the electrodes are wound or stacked to obtain an electrode assembly. The electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a secondary battery is obtained.

[0069] The positive electrode sheet of this application typically includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector. The positive electrode film layer includes a positive electrode active material, which can be any of the existing disclosed positive electrode active materials or a positive electrode active material optimized based on the existing ones.

[0070] This application does not impose any particular limitation on the type of positive electrode active material for the positive electrode sheet. As an example, the positive electrode active material in this application includes nickel-cobalt-based positive electrode materials and / or lithium iron phosphate materials. Specifically, the nickel-cobalt-based positive electrode materials include high-nickel nickel-cobalt-based positive electrode materials and medium-nickel nickel-cobalt-based positive electrode materials; wherein, based on the total molar content of non-lithium metal elements, the molar content of nickel in the high-nickel nickel-cobalt-based positive electrode material is more than 70%, and the molar content of nickel in the medium-nickel nickel-cobalt-based positive electrode material is 50% to 70%.

[0071] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive electrode active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, rolling, cutting and other processes.

[0072] In this application, the binder is used to improve the adhesion between positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. This application does not impose any particular limitation on the type of binder for the positive electrode sheet; the binder can be any conventional choice in the battery industry. Specifically, the binder can be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVC), styrene-butadiene rubber (SBR), polyacrylonitrile (PCN), polyimide (PI), polyacrylic acid (PCC), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC), or sodium alginate.

[0073] This application does not impose any particular restrictions on the positive electrode current collector, as long as it is conductive and will not cause adverse chemical changes in the battery, and can be made of, for example: stainless steel, aluminum, nickel, titanium, sintered carbon; or aluminum or stainless steel that has been surface treated with one of carbon, nickel, titanium, silver, etc.

[0074] The negative electrode sheet of this application includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector. The negative electrode active material layer includes a silicon-based material. This application does not specifically limit the type of silicon-based material; the silicon-based material can be a silicon-carbon material and / or a silicon-oxygen material. As an example, the silicon-based material can be one or more of silicon-carbon composite negative electrode materials, silicon suboxide negative electrode materials, modified silicon suboxide negative electrode materials, and nano-silicon materials. The negative electrode active material in the negative electrode active material layer may also optionally include one or more of artificial graphite, natural graphite, and hard carbon.

[0075] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, rolling, cutting and other processes.

[0076] This application does not specifically limit the type of negative electrode conductive agent. In some embodiments, as an example, the negative electrode conductive agent can be one or more of conventional negative electrode conductive agents such as acetylene black and carbon nanotubes.

[0077] This application does not impose specific limitations on the type of negative electrode binder. In some embodiments, as an example, the binder may be one or more of conventional negative electrode binders such as styrene-butadiene rubber latex (SBR), polyvinylidene fluoride (PVDF), polyacrylic acid (PCC), and sodium carboxymethyl cellulose (CMC).

[0078] This application does not specifically limit the type of negative electrode current collector. In some embodiments, as an example, the negative electrode current collector can be one of the conventional negative electrode current collectors such as copper foil.

[0079] The electrolyte in this application serves to conduct ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte; it can be selected according to requirements. As an example, the electrolyte in this application can be any electrolyte suitable for electrochemical energy storage devices in the art. The electrolyte includes an electrolyte and a solvent; the electrolyte typically includes a lithium salt, and additives may also be added to the electrolyte.

[0080] Specifically, lithium salts include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate (LiPF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiCsF6), lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate, lithium dioxalate borate (LiPOP), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).

[0081] Specifically, the solvents mentioned above include at least one of ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (PC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MC), ethyl acetate (EC), propyl acetate (PC), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MP), ethyl butyrate (EP), 1,4-butyrolactone (GPL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0082] In some implementations, as an example, the additive may be a conventional electrolyte additive such as fluoroethylene carbonate (FEC), chloroethylene carbonate (CEC), or vinylene carbonate (VC).

[0083] In some embodiments, the secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0084] In some embodiments, as an example, the diaphragm can be one of PP, PE, or PP / PF; the diaphragm can also be a structure in which a coating is formed on the surface of the base film, wherein the base film coating can be one of PP, PE, or PP / PF, and the coating can be an inorganic coating and / or an organic coating. The inorganic coating can be selected from alumina ceramic layers, osmium silicate, etc., and the organic coating can be selected from PVDF, etc.

[0085] According to a third aspect of this application, an electrical device is provided, including a battery; which is the aforementioned battery. This silicon-carbon battery has high energy density, high cycle stability, fast charge / discharge rate, and reliable safety.

[0086] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0087] The raw materials used in the embodiments of this application are all existing technologies and are commercially available.

[0088] Preparation methods of silicon-based materials:

[0089] Porous carbon material was used as the carbon matrix and added to a rotary kiln. First, it was sieved using an air classifier with an internal pressure of 900 Pa. Nitrogen gas was introduced at a flow rate of 15 L / min to remove oxygen. The calcination heating rate was 5 °C / min, the temperature was 480 °C, and the rotary kiln rotation speed was 2 rpm. While maintaining a constant calcination temperature, a mixed gas consisting of nitrogen and silane in a 1:2 volume ratio was introduced at a flow rate of 0.2 L / min for 95 min. After the reaction is complete, the silane gas is turned off, and only nitrogen gas is introduced. The silicon-based material is calcined in a nitrogen atmosphere at a temperature of 550°C for 100 minutes. When the temperature fluctuation gradually stabilizes, acetylene gas is introduced to carry out the reaction at a flow rate of 2 L / min. The deposition temperature is 500°C and the deposition time is 12 hours. After the reaction is complete, the gas is turned off, and the material is allowed to cool naturally in a nitrogen atmosphere. After the temperature has completely cooled, the material is demagnetized to obtain a silicon-based material with a carbon coating.

[0090] Example 1

[0091] Step S1, Positive Electrode Preparation: The positive electrode active material, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are mixed at a mass ratio of 98.2:0.7:1.1. N-methylpyrrolidone (NMP) solvent is added, and the mixture is stirred under vacuum until homogeneous to obtain a positive electrode slurry. The positive electrode slurry is coated onto one surface of the positive electrode current collector aluminum foil, and then onto the other side. After drying at room temperature (25℃), it is transferred to an oven and dried at 100℃ for 1 hour. Then, it is cold-pressed (roller pressing temperature 25℃) and slit to obtain the positive electrode sheet. The areal density of the positive electrode sheet is 420 g / m³. 2 The compacted density is 3.55 g / cm³. 3 .

[0092] Step S2, Negative Electrode Preparation: Artificial graphite with a D50 particle size of 10 μm, silicon-based materials, conductive agents acetylene black and SWCNT, thickener CMC, and binder SBR are mixed at a mass ratio of 81.12:14.88:0.95:0.05:1.2:1.8. Deionized water is added as solvent, and the solid content is controlled at 55%. The mixture is stirred under vacuum until homogeneous. During kneading, the stirring speed is 70 rpm, the dispersion time is 5 hours, and then it is allowed to stand for 1 hour to obtain the negative electrode slurry. The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil (controlling surface density). After drying at room temperature (25℃), it is transferred to an oven and dried at 100℃ for 1 hour. Then, it is cold-pressed (roller pressing temperature is 25℃) and slit to obtain the negative electrode sheet. The surface density of the negative electrode sheet is 160 g / m³. 2 .

[0093] Step S3, Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, fluoroethylene carbonate (FEC) is added (the mass percentage of the additive is 2%). Next, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0094] Step S4, Preparation of the separator: Select a polypropylene membrane coated with an alumina coating as the separator for the lithium-ion battery.

[0095] Step S5, Assembly and Formation: Stack the above positive electrode sheet, separator, and negative electrode sheet in sequence, so that the separator is between the positive and negative electrode sheets to play a role in isolation, and then wind them to obtain a bare cell; place the bare cell in an outer packaging shell, dry it, inject electrolyte, and then go through vacuum sealing, standing, formation, and shaping processes to obtain a lithium-ion battery.

[0096] Example 2

[0097] The difference between Example 2 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 1300 Pa, the kneading revolution speed in step S2 is replaced with 50 rpm, the dispersion time is 2.5 h, and then it is left to stand for 2 h; the cold pressing pressure is replaced with 23 T; all other steps are the same.

[0098] Example 3

[0099] The difference between Example 3 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 700 Pa, the kneading revolution speed in step S2 is replaced with 45 rpm, the dispersion time is 2.5 h, and then it is left to stand for 2 h; the cold pressing pressure is replaced with 15 T; all other steps are the same.

[0100] Example 4

[0101] The difference between Example 4 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 600 Pa, the kneading revolution speed in step S2 is replaced with 65 rpm, the dispersion time is 4 h, and then it is left to stand for 1.5 h; the cold pressing pressure is replaced with 13 T; all other steps are the same.

[0102] Example 5

[0103] The difference between Example 5 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 650 Pa, the kneading revolution speed in step S2 is replaced with 55 rpm, the dispersion time is 3 h, the standing time is 2 h, and the cold pressing pressure is replaced with 12 T; all other steps are the same.

[0104] Example 6

[0105] The difference between Example 6 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 420 Pa, the kneading revolution speed in step S2 is replaced with 55 rpm, the dispersion time is 3.5 h, the standing time is 1.5 h, and the cold pressing pressure is replaced with 11 T; all other steps are the same.

[0106] Example 7

[0107] The difference between Example 7 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 1400 Pa, the kneading revolution speed in step S2 is replaced with 15 rpm, the dispersion time is 1 h, and the standing time is 4 h; the cold pressing pressure is replaced with 24 T; all other steps are the same.

[0108] Example 8

[0109] The difference between Example 8 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 500 Pa, the kneading revolution speed in step S2 is replaced with 45 rpm, the dispersion time is 2.5 h, and the standing time is 2 h; the cold pressing pressure is replaced with 11 T; all other steps are the same.

[0110] Example 9

[0111] The difference between Example 9 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 300 Pa, the kneading revolution speed in step S2 is replaced with 24 rpm, the dispersion time is 1.5 h, the standing time is 2.5 h, and the cold pressing pressure is replaced with 8 T; all other steps are the same.

[0112] Example 10

[0113] The difference between Example 10 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 100 Pa, the kneading revolution speed in step S2 is replaced with 30 rpm, the dispersion time is 2 h, the standing time is 2.5 h, and the cold pressing pressure is replaced with 5 T; all other steps are the same.

[0114] Example 11

[0115] The difference between Example 11 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 1600 Pa, the kneading revolution speed in step S2 is replaced with 5 rpm, the dispersion time is 1 h, and the standing time is 3 h; the cold pressing pressure is replaced with 26 T; all other steps are the same.

[0116] Example 12

[0117] The difference between Example 12 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 2000 Pa, the kneading revolution speed in step S2 is replaced with 10 rpm, the dispersion time is 1 h, and the standing time is 4 h; the cold pressing pressure is replaced with 30 T; all other steps are the same.

[0118] Example 13

[0119] The difference between Example 13 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 2200 Pa, the kneading revolution speed in step S2 is replaced with 5 rpm, the dispersion time is 1 h, and the standing time is 5 h; the cold pressing pressure is replaced with 35 T; all other steps are the same.

[0120] Example 14

[0121] The difference between Example 14 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 1700 Pa, the kneading revolution speed in step S2 is replaced with 3 rpm, the dispersion time is 0.4 h, and the standing time is 6 h; the cold pressing pressure is replaced with 27 T; all other steps are the same.

[0122] Example 15

[0123] The difference between Example 15 and Example 1 is that the type of positive electrode active material is different in S1, and the pressure inside the classifier during the preparation of silicon-based material in S2 is 850 Pa. The kneading revolution speed in step S2 is replaced with 70 rpm, the dispersion time is 4.5 h, and the standing time is 1 h. The cold pressing pressure is replaced with 18 T. All other steps are the same.

[0124] Example 16

[0125] The difference between Example 16 and Example 1 is that the type of positive electrode active material is different in S1, and the pressure inside the classifier during the preparation of silicon-based material in S2 is 150 Pa. The kneading revolution speed in step S2 is replaced with 35 rpm, the dispersion time is 2 h, and the standing time is 2.5 h. The cold pressing pressure is replaced with 6 T. All other steps are the same.

[0126] Example 17

[0127] The difference between Example 17 and Example 1 is that the type of positive electrode active material is different in S1, and the pressure inside the classifier during the preparation of silicon-based material in S2 is 2000 Pa. The kneading revolution speed in step S2 is replaced with 15 rpm, the dispersion time is 1 h, and the standing time is 4 h. The cold pressing pressure is replaced with 30 T. All other steps are the same.

[0128] Example 18

[0129] The difference between Example 18 and Example 1 is that in S1, the positive electrode active material is lithium iron phosphate; in S2, the mass ratio of artificial graphite with a D50 particle size of 10 μm, silicon-based material, conductive agent acetylene black, conductive agent SWCNT, thickener CMC, and binder SBR is 85.824:10.176:0.95:0.05:1.2:1.8; the pressure inside the classifier when preparing the silicon-based material is 1000 Pa; the kneading revolution speed in step S2 is replaced with 70 rpm; the dispersion time is 5 h; and the standing time is 1 h; the cold pressing pressure is replaced with 20 T; all other steps are the same.

[0130] Example 19

[0131] The difference between Example 19 and Example 1 is that in S1, the positive electrode active material is lithium iron phosphate; in S2, the mass ratio of artificial graphite with a D50 particle size of 10 μm, silicon-based material, conductive agent acetylene black, conductive agent SWCNT, thickener CMC, and binder SBR is 85.824:10.176:0.95:0.05:1.2:1.8; the pressure inside the classifier when preparing the silicon-based material is 500 Pa; the kneading revolution speed in step S2 is replaced with 15 rpm; the dispersion time is 1 h; and the standing time is 4 h; the cold pressing pressure is replaced with 11 T; all other steps are the same.

[0132] Example 20

[0133] The difference between Example 20 and Example 1 is that in S1, the positive electrode active material is lithium iron phosphate; in S2, the mass ratio of artificial graphite with a D50 particle size of 10 μm, silicon-based material, conductive agent acetylene black, conductive agent SWCNT, thickener CMC, and binder SBR is 85.824:10.176:0.95:0.05:1.2:1.8; the pressure inside the classifier when preparing the silicon-based material is 100 Pa; the kneading revolution speed in step S2 is replaced with 20 rpm; the dispersion time is 2.5 h; and the standing time is 2 h; the cold pressing pressure is replaced with 5 T; all other steps are the same.

[0134] Example 21

[0135] The difference between Example 21 and Example 1 is that in S2, the artificial graphite with a D50 particle size of 10 μm, silicon-based material, conductive agent acetylene black, conductive agent SWCNT, thickener CMC, and binder SBR are in a mass ratio of 72.192:23.808:0.95:0.05:1.2:1.8; the pressure inside the classifier when preparing the silicon-based material is 1000 Pa; the kneading revolution speed in step S2 is replaced with 65 rpm; the dispersion time is 4 h; and the standing time is 1.5 h; the cold pressing pressure is replaced with 20 T; all other steps are the same.

[0136] Example 22

[0137] The difference between Example 22 and Example 1 is that in S2, the artificial graphite with a D50 particle size of 10 μm, silicon-based material, conductive agent acetylene black, conductive agent SWCNT, thickener CMC, and binder SBR are in a mass ratio of 37.248:58.752:0.95:0.05:1.2:1.8; the pressure inside the classifier when preparing the silicon-based material is 1100 Pa; the kneading revolution speed in step S2 is replaced with 60 rpm; the dispersion time is 3.5 h; and the standing time is 1.5 h; the cold pressing pressure is replaced with 21 T; all other steps are the same.

[0138] Example 23

[0139] The difference between Example 23 and Example 1 is that in S2, the artificial graphite with a D50 particle size of 10 μm, silicon-based material, conductive agent acetylene black, conductive agent SWCNT, thickener CMC, and binder SBR are in a mass ratio of 85.248:10.752:0.95:0.05:1.2:1.8; the pressure inside the classifier when preparing the silicon-based material is 780 Pa; the kneading revolution speed in step S2 is replaced with 70 rpm; the dispersion time is 5 h; and the standing time is 1 h; the cold pressing pressure is replaced with 17 T; all other steps are the same.

[0140] Example 24

[0141] The difference between Example 24 and Example 1 is that in S2, the artificial graphite with a D50 particle size of 10 μm, silicon-based material, conductive agent acetylene black, conductive agent SWCNT, thickener CMC, and binder SBR are in a mass ratio of 56.256:39.744:0.95:0.05:1.2:1.8; the pressure inside the classifier when preparing the silicon-based material is 900 Pa; the kneading revolution speed in step S2 is replaced with 65 rpm; the dispersion time is 4 h; and the standing time is 1.5 h; the cold pressing pressure is replaced with 19 T; all other steps are the same.

[0142] Example 25

[0143] The difference between Example 25 and Example 1 is that in S2, the artificial graphite with a D50 particle size of 10 μm, silicon-based material, conductive agent acetylene black, conductive agent SWCNT, thickener CMC, and binder SBR are in a mass ratio of 56.256:39.744:0.95:0.05:1.2:1.8; the pressure inside the classifier when preparing the silicon-based material is 450 Pa; the kneading revolution speed in step S2 is replaced with 35 rpm; the dispersion time is 2 h; and the standing time is 2.5 h; the cold pressing pressure is replaced with 11 T; all other steps are the same.

[0144] Example 26

[0145] The difference between Example 26 and Example 1 is that in S2, artificial graphite with a D50 particle size of 10 μm, silicon-based material, conductive agent acetylene black, conductive agent SWCNT, thickener CMC, and binder SBR are in a mass ratio of 56.256:39.744:0.95:0.05:1.2:1.8; the pressure inside the classifier when preparing the silicon-based material is 360 Pa; the kneading revolution speed in step S2 is replaced with 20 rpm; the dispersion time is 1.5 h; and the standing time is 2.5 h; the cold pressing pressure is replaced with 10 T; all other steps are the same.

[0146] Example 27

[0147] The difference between Example 27 and Example 1 is that, in step S2, the pressure inside the classifier during the preparation of the silicon-based material is 780 Pa; the kneading revolution speed in step S2 is replaced with 70 rpm; the dispersion time is 5 h; and the standing time is 1 h. The cold pressing pressure is replaced with 17 T. Furthermore, after cold pressing, a first negative electrode active layer is formed on the surface of the negative electrode current collector; then, a second negative electrode active layer is formed on the side of the first negative electrode active layer away from the negative electrode current collector. The preparation method of the second negative electrode active layer is as follows:

[0148] Artificial graphite with a D50 particle size of 10 μm, conductive agent acetylene black, conductive agent SWCNT, thickener CMC, and binder SBR were mixed at a mass ratio of 96:0.95:0.05:1.2:1.8. Deionized water was added as solvent, and the solid content was controlled at 55%. The mixture was stirred in a vacuum mixer until it became homogeneous. During the kneading process, the stirring speed was 60 rpm, the dispersion time was 4 h, and then it was allowed to stand for 1 h to obtain the second negative electrode slurry. The second negative electrode slurry was coated on the surface of the first negative electrode active layer, dried at room temperature (25 °C), and then transferred to an oven to continue drying at 100 °C for 1 h. After that, it was cold-pressed (roller pressing temperature was 25 °C) and slit to obtain the negative electrode sheet. The thickness ratio of the first negative electrode active layer and the second negative electrode active layer was 1:1.

[0149] All other steps are the same.

[0150] Example 28

[0151] The difference between Example 28 and Example 1 is that a carbon layer with a thickness of 0.05 μm exists between the negative electrode current collector and the negative electrode active layer.

[0152] Example 29

[0153] The difference between Example 29 and Example 28 is that the thickness of the carbon layer is 1.2 μm.

[0154] Example 30

[0155] The difference between Example 30 and Example 28 is that the thickness of the carbon layer is 2 μm.

[0156] Example 31

[0157] The difference between Example 31 and Example 28 is that the thickness of the carbon layer is 2.5 μm.

[0158] Comparative Example 1

[0159] The difference between Comparative Example 1 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 60 Pa, the kneading revolution speed in step S2 is replaced with 3 rpm, the dispersion time is 0.4 h, the standing time is 6 h, the cold pressing pressure is replaced with 4 T, and all other steps are the same.

[0160] Comparative Example 2

[0161] The difference between Comparative Example 2 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 2300 Pa, the kneading revolution speed in step S2 is replaced with 75 rpm, the dispersion time is 5.5 h, no standing is allowed, and the cold pressing pressure is replaced with 40 T; all other steps are the same.

[0162] Comparative Example 3

[0163] The difference between Comparative Example 3 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 180 Pa, the kneading revolution speed in step S2 is replaced with 10 rpm, the dispersion time is 1 h, the standing time is 4 h, the cold pressing pressure is replaced with 6 T, and all other steps are the same.

[0164] Comparative Example 4

[0165] The difference between Comparative Example 4 and Example 1 is that the pressure inside the classifier during the preparation of silicon-based materials is 2000 Pa, the kneading revolution speed in step S2 is replaced with 70 rpm, the dispersion time is 5 h, the standing time is 1 h, the cold pressing pressure is replaced with 30 T, and all other steps are the same.

[0166] Comparative Example 5

[0167] The difference between Comparative Example 5 and Example 1 is that the type of positive electrode active material is different in S1; in S2, the pressure inside the classifier during the preparation of silicon-based materials is 150 Pa, the kneading revolution speed in step S2 is replaced with 8 rpm, the dispersion time is 1 h; and the standing time is 4 h; the cold pressing pressure is replaced with 6 T; all other steps are the same.

[0168] Comparative Example 6

[0169] The difference between Comparative Example 6 and Example 1 is that the type of positive electrode active material is different in S1; in S2, the pressure inside the classifier during the preparation of silicon-based materials is 2400 Pa, the kneading revolution speed in step S2 is replaced with 78 rpm, the dispersion time is 6 h; no standing is allowed; the cold pressing pressure is replaced with 45 T; all other steps are the same.

[0170] Comparative Example 7

[0171] The difference between Comparative Example 7 and Example 1 is that the type of positive electrode active material is different in S1; in S2, the pressure inside the classifier during the preparation of silicon-based materials is 0 Pa, the kneading revolution speed in step S2 is replaced with 3 rpm, the dispersion time is 0.6 h, and the standing time is 5.5 h; the cold pressing pressure is replaced with 3 T; all other steps are the same.

[0172] Comparative Example 8

[0173] The difference between Comparative Example 8 and Example 1 is that the type of positive electrode active material is different in S1; in S2, the pressure inside the classifier during the preparation of silicon-based materials is 2000 Pa, the kneading revolution speed in step S2 is replaced with 70 rpm, the dispersion time is 4.5 h, and the standing time is 1 h; the cold pressing pressure is replaced with 30 T; all other steps are the same.

[0174] Performance testing:

[0175] The performance of the lithium-ion batteries prepared in each embodiment and comparative example was tested as follows, and the results are shown in Table 1.

[0176] 1. Method for detecting silicon content in the negative electrode active layer:

[0177] (1) Pretreatment: Discharge the battery at 0.33C to the lower limit voltage of 2.5V to obtain an empty battery. Disassemble the battery and take the electrode sheet of the lithium-ion battery in the empty state. Soak it in dimethyl carbonate (DMC) solution at room temperature for 4 hours. After soaking, take out the electrode sheet and dry it in a vacuum environment. Divide the negative electrode sheet into three regions on an average basis (length direction). Each region is divided into 4 test areas, for a total of 12 silicon content test areas. The test area of ​​each test area is 70mm×70mm. Use a ceramic knife to scrape the negative electrode material powder on the surface of the electrode sheet in each test area and test the mass content of silicon in the test area. The maximum mass content of silicon in all test areas is c. max The minimum mass content of silicon in all tested regions is c. min The ratio between the maximum and minimum values ​​is c, and c = c max / c min ;

[0178] (2) The silicon content in the negative electrode sheet was tested by the alkaline dissolution-ICP method. The negative electrode active material layer powder was scraped off. The powder sample was weighed and placed in a nickel crucible pre-filled with potassium hydroxide. A small amount of potassium hydroxide was added to cover the sample surface, and two drops of ethanol were added. The sample was heated on an electric furnace until the potassium hydroxide melted and dehydrated. Then, it was transferred to a muffle furnace at 1100°C and kept at the melting temperature for 8 hours. The nickel crucible was removed and cooled slightly. The sample was placed in a 300 mL plastic beaker and extracted with hot water at 80°C. After the reaction, the sample was washed out of the crucible. HCl was added to the extract for acidification, and hydrogen peroxide and hydrochloric acid were added to form a mixed acid to make the silicon-containing compound convert to silicon ions more thoroughly. After cooling, the sample was washed out with water and transferred to a 100 mL volumetric flask. The volume was adjusted and the sample was shaken. After standing, the solution was separated into another 100 mL volumetric flask, adjusted to volume, shaken, and allowed to stand until clear to obtain the test solution. Simultaneously, a blank solution was prepared as a control. No powder was added to the blank solution. The blank sample control was prepared according to the operating procedure to eliminate any potential influences during the operation. ICP testing was performed on the test solution. The elemental detection wavelength was selected, and the experimental conditions were set: based on the sample characteristics and the ICP testing of the test solution, the Si elemental detection wavelength of 288.158 nm was selected. The Si content of the element was determined by ICP testing; the detection results are shown in Table 1.

[0179] 2. Method for detecting the porosity of the negative electrode active layer:

[0180] (1) Pretreatment: Discharge the battery at 0.33C to the lower limit voltage of 2.5V to obtain an empty battery. Take the empty battery, disassemble the electrode, soak the electrode in dimethyl carbonate (DMC) solution for 4 hours; and air dry.

[0181] (2) Subsequently, the electrode was cut into round pieces with a diameter of 12 mm using an electrode punching machine. At the same time, the thickness of the electrode and the current collector was measured with a thickness gauge, which were h1 and h2 respectively. The mass was weighed with a balance with an accuracy of 0.00001 g and recorded as m1. According to the formula v=πr 2 Calculate the volume v of the cut electrode (h1-h2); immerse the electrode in a sealed container with a certain volume of hexadecane for 1 hour (the volume of hexadecane in the sealed solution is not required, but the amount must be sufficient to completely submerge the electrode); after 1 hour, remove the electrode with tweezers and place it on filter paper to absorb the water until a constant weight is reached (approximately 1 hour). Weigh the electrode using a balance and record the mass as m2. Calculate the porosity using the formula X / v, where X = (m2-m1) / ρ, and ρ is the density of hexadecane, 0.7734 g / cm³. 3 .

[0182] 3. Charging DCR test method:

[0183] (1) The prepared lithium-ion battery was placed at room temperature (25°C) and left to stand for 4 hours;

[0184] (2) Perform 3 standard cycles at a current of 1 / 3C; record the standard capacity C of the battery. The standard cycle steps are: charge the lithium-ion battery at a constant current of 0.33C to the upper limit voltage, charge it at a constant voltage to 0.05C, and then discharge it at a constant current of 0.33C to the lower limit voltage of 2.5V to obtain the standard capacity C.

[0185] (3) Adjust to the test temperature of 25℃ and let stand for 4 hours until thermal equilibrium is reached;

[0186] (4) Charge the battery to 50% SOC at a discharge rate of 1 / 3C, let it stand for 2 hours, and record the voltage U4 after standing.

[0187] (5) Charge the battery with a current of 1C for 10s, record the battery voltage U3 after the charging stabilizes, and calculate the DC internal resistance DCR according to the formula R2=(U3-U4) / I.

[0188] The upper limit voltage for nickel-cobalt based cathode materials is 4.25V; the upper limit voltage for lithium iron phosphate is 3.65V.

[0189] 4. Performance 2: Poor electrolyte wetting effect - Electrode wettability test using the coating method:

[0190] (1) Use a ceramic knife to cut the negative electrode sheet in the example and comparative example into 12cm×4cm for later use. At the same time, cut the PET-based-EVA hot melt adhesive composite film into the same size as the electrode sheet. Then use a punching pliers to make three 2mm round holes on the composite film, with each round hole spaced 3-4cm apart. Spread the punched composite film on the surface of the electrode sheet and use a plastic sealing machine to fix the coated electrode sheet. The plastic sealing temperature of the negative electrode sheet is 90℃.

[0191] (2) Fix the coated electrode flat on a smooth and flat glass table in a low-humidity environment. Use a dropper to add sufficient electrolyte (3 drops are enough, add 0.3 mL) to the round hole. Soak for 3 minutes, wipe off the electrolyte, measure the diameter of the electrolyte wetting area at the same time, and take the average value.

[0192] Table 1

[0193]

[0194]

[0195] As shown in Table 1, by adjusting the uniformity coefficient c of silicon distribution in the negative electrode active layer and the porosity p of the negative electrode active layer to satisfy: 0.05≤c×p≤1.1, this application helps to control the 50% SOC-charging DCR of high-nickel nickel-cobalt based batteries to within 30mΩ, the 50% SOC-charging DCR of medium-nickel nickel-cobalt based batteries to within 43mΩ, and the 50% SOC-charging DCR of lithium iron phosphate batteries to within 32mΩ; thereby helping to improve the dynamic performance of the batteries.

[0196] The excessively large c×p values ​​in Comparative Examples 1, 3, 5, and 7 indicate poor uniformity of silicon distribution in the negative electrode active layer and a relatively loose structure, resulting in poor kinetic consistency of the negative electrode sheet and poor electron transport performance. Consequently, the 50% SOC-charge DCR of the battery is significantly higher, and the overall kinetic performance of the battery is poor.

[0197] The small c×p values ​​in Comparative Examples 2, 4, 6, and 8 indicate that the structure of the negative electrode active layer is too dense, resulting in poor electrolyte wettability and high ion diffusion resistance. This leads to an excessively small electrode wettability diameter or a high 50% SOC-charge DCR, affecting the battery's kinetic performance.

[0198] In addition, comparing the performance test results of Examples 1-6 with those of Example 7, it can be found that when c satisfies: 1.05≤c≤1.2, the 50% SOC-charging DCR of the battery is smaller, indicating that the battery has better dynamic performance.

[0199] Comparing the performance test results of Examples 1-6 with Example 8, it can be found that when the product of c and p satisfies: 0.095≤c×p≤0.56, the 50% SOC-charging DCR of the battery is significantly smaller, which is more conducive to improving the dynamic performance of the battery.

[0200] Comparing the performance test results of Examples 1-6 with Examples 9-14, it can be found that when the product of c and p satisfies: 0.095≤c×p≤0.56, and c satisfies: 1.05≤c≤1.2, and p satisfies: 8%≤p≤50%, the dynamic performance of the battery can be further improved.

[0201] Comparing the performance test results of Examples 21, 22, 24, 25 and 26, it can be found that when the mass content of silicon in the negative electrode active layer is greater than or equal to 12%, controlling 0.05≤c×p≤0.635 helps to reduce the SOC-charging DCR by 50% and improve the dynamic performance of the battery.

[0202] Comparing the performance test results of Example 1 and Example 27, it can be found that when the negative electrode active layer includes a first negative electrode active layer and a second negative electrode active layer, and the types of negative electrode active materials in the two are different, it helps to improve the dynamic performance of the battery.

[0203] Comparing the performance test results of Examples 1 and 28-30, it can be found that setting a carbon layer between the negative electrode active layer and the negative electrode current collector also helps to improve the kinetic performance of the battery.

[0204] In addition, comparing the performance test results of Examples 28-30 with those of Example 31, it can be found that controlling the thickness of the carbon layer to be 0.05μm-2μm helps to further improve the kinetic performance of the battery.

[0205] It should be noted that the terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in a sequence other than those described herein.

[0206] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A negative electrode sheet, characterized in that, The anode active layer includes a negative electrode material; the negative electrode material includes a negative electrode active material; the negative electrode active material includes a silicon-based material and a carbon material; the uniformity coefficient of silicon element distribution in the silicon-based material in the negative electrode active layer and the porosity of the negative electrode active layer satisfy Equation I: 0.05≤c×p≤1.1 Formula I; In Formula I, c is the uniformity coefficient of silicon element distribution in the negative electrode active layer of the silicon-based material; p is the porosity of the negative electrode active layer; c=c max / c min Formula II; In Equation II, c max c is the maximum mass content of silicon in all tested regions. min The minimum mass content of silicon element in all regions to be tested is n, where n is an integer greater than or equal to 3.

2. The negative electrode sheet according to claim 1, characterized in that, In Equation I, 0.095 ≤ c × p ≤ 0.

56.

3. The negative electrode sheet according to claim 1, characterized in that, At least one of the following conditions must be met: (1) The c satisfies: 1.05≤c≤1.5; (2) The p satisfies: 3.5%≤p≤85%.

4. The negative electrode sheet according to claim 3, characterized in that, At least one of the following conditions must be met: (1) The c satisfies: 1.05 ≤ c ≤ 1.2; (2) The p satisfies: 8%≤p≤50%.

5. The negative electrode sheet according to claim 1, characterized in that, The silicon content of the silicon element in the silicon-based material in the negative electrode active layer is less than or equal to 12%.

6. The negative electrode sheet according to claim 5, characterized in that, Equation I satisfies: 0.095≤c×p≤0.

594.

7. The negative electrode sheet according to claim 5 or 6, characterized in that, The silicon element in the silicon-based material has a mass content of greater than or equal to 5% and less than or equal to 7.5% in the negative electrode active layer.

8. The negative electrode sheet according to claim 1, characterized in that, The silicon element in the silicon-based material has a mass content of greater than or equal to 12% in the negative electrode active layer.

9. The negative electrode sheet according to claim 8, characterized in that, Equation I satisfies: 0.05≤c×p≤0.

635.

10. The negative electrode sheet according to claim 8 or 9, characterized in that, The silicon element in the silicon-based material has a mass content of greater than or equal to 12% and less than or equal to 25% in the negative electrode active layer.

11. The negative electrode sheet according to any one of claims 1 to 4, characterized in that, The silicon-based material is selected from at least one of silicon-carbon composite materials, silicon suboxide, and nano-silicon. And / or, the carbon material is selected from at least one of artificial graphite and natural graphite.

12. The negative electrode sheet according to any one of claims 1 to 4, characterized in that, The median particle size Dv50 of the negative electrode material satisfies: 4μm≤Dv50≤10μm.

13. The negative electrode sheet according to claim 12, characterized in that, The volume median particle size D of the negative electrode material V 50 satisfies: 5μm≤D V 50≤9μm.

14. The negative electrode sheet according to any one of claims 1 to 4, characterized in that, The compacted density of the negative electrode sheet is greater than or equal to 1.10 g / cm³. 3 Less than or equal to 1.75 g / cm³ 3 .

15. The negative electrode sheet according to any one of claims 1 to 4, characterized in that, The negative electrode sheet includes a negative electrode current collector, the negative electrode active layer is located on at least one side of the negative electrode current collector, and satisfies at least one of the following conditions: (1) The average roughness depth Rz of the surface of the negative electrode current collector is greater than or equal to 0.5 μm and less than or equal to 3 μm; (2) The negative electrode current collector is a copper foil or a copper alloy foil.

16. The negative electrode sheet according to claim 15, characterized in that, The negative electrode sheet also includes a carbon layer, which is located between the negative electrode current collector and the negative electrode active layer.

17. The negative electrode sheet according to claim 16, characterized in that, The thickness of the carbon layer is greater than or equal to 0.5 μm and less than or equal to 2 μm.

18. The negative electrode sheet according to claim 15, characterized in that, The negative electrode active layer includes a first negative electrode active layer and a second negative electrode active layer; the first negative electrode active layer and the second negative electrode active layer are sequentially disposed on the surface of the negative electrode current collector from the surface close to the negative electrode current collector to the surface away from the negative electrode current collector; The first negative electrode active layer includes a first negative electrode active material, which includes a first silicon-based material and / or a first carbon material; The second negative electrode active layer includes a second negative electrode active material, which includes a second silicon-based material and / or a second carbon material; The average particle size of the first negative electrode active material is greater than that of the second negative electrode active material.

19. The negative electrode sheet according to claim 18, characterized in that, At least one of the following conditions must be met: (1) The first carbon material and the second carbon material are each independently selected from at least one of artificial graphite and natural graphite; (2) The first silicon-based material and the second silicon-based material are each independently selected from at least one of silicon-carbon composite materials, carbon-coated silicon-carbon composite materials, silicon suboxide, carbon-coated silicon suboxide, and nano-silicon.

20. The negative electrode sheet according to claim 18, characterized in that, The mass content of silicon in the second negative electrode active layer is greater than that in the first negative electrode active layer.

21. The negative electrode sheet according to claim 18, characterized in that, The mass content of silicon in the second negative electrode active layer is less than that in the first negative electrode active layer.

22. The negative electrode sheet according to claim 21, characterized in that, The second negative electrode active material is the second carbon material; the first negative electrode active material is a compound of the first carbon material and the first silicon-based material.

23. A battery comprising a cell, the cell including a positive electrode and a negative electrode; characterized in that, The negative electrode is any one of claims 1 to 22.

24. The battery according to claim 23, characterized in that, The positive electrode sheet includes a positive electrode active layer; the positive electrode active layer includes a positive electrode active material; the positive electrode active material includes at least one of nickel-cobalt based positive electrode material and lithium iron phosphate material.

25. The battery according to claim 24, characterized in that, The positive electrode active material includes a nickel-cobalt based positive electrode material, the structural formula of which is Li. a Ni b Co x Mn d M e O2; where 0.75≤ a ≤1.2, b Greater than or equal to 0.8 b + x + d =1, 0≤ e ≤0.2; M is selected from at least one of B, Zr, Ti, Si, Mo, La, Ce, Te, Nb, Ta, Al, W, Sr, V, Y, and Mg; And / or, the positive electrode active material includes a nickel-cobalt based positive electrode material, and 0.095≤c×p≤0.451; And / or, the positive electrode active material includes lithium iron phosphate material, wherein the structural formula of the lithium iron phosphate material is LiFe 1-u M' u PO v Q w Where u≤0.1, 3.85≤v≤4, 0≤w≤0.05, and M' is selected from at least one of Mn, Ni, Co, Cr, Cu, Bi, and Sb; And / or, the positive electrode active material includes lithium iron phosphate material, and 0.05≤c×p≤0.7227.

26. The battery according to any one of claims 23 to 25, characterized in that, The battery cell is a cylindrical battery cell.

27. The battery according to any one of claims 23 to 25, characterized in that, The battery also includes an electrolyte; The electrolyte has an ionic conductivity of 8 mS / cm to 15 mS / cm at 25°C.

28. The battery according to claim 27, characterized in that, The electrolyte comprises lithium salt, solvent, and additives, and satisfies at least one of the following conditions: (1) The lithium salt includes at least one of lithium difluorosulfonylimide, lithium difluorooxalate borate, and lithium hexafluorophosphate; (2) The solvent is selected from at least one of cyclic carbonates, chain carbonates and chain carboxylic esters; (3) The additives include fluoroethylene carbonate; (4) The concentration of the lithium salt in the electrolyte is 0.8 mol / L to 1.2 mol / L; (5) The mass percentage of the additive in the electrolyte is 1% to 10%.

29. An electrical device, comprising a battery, characterized in that, The battery is the battery according to any one of claims 23 to 28.

Citation Information

Patent Citations

  • Lithium ion secondary battery

    CN116613302A

  • Negative pole piece, electrochemical device and electronic device

    CN116802852A